THE POTENTIAL OF PROBLEM‐BASED LEARNING TO ENHANCE ENGINEERING EDUCATION IN AFRICAN UNIVERSITIES. (26th December 2019) - Abbott, D.; Chipika, S.; Wilson, G.
Abstract: Engineering education underpins local capacity. As such, it forms a key component of sustainable engineering for development. While education is needed at all levels, this paper focuses on the tertiary level where it is assumed that graduating students aspire to become professional engineers. In much of Africa, however, university engineering education is criticised for being little changed since the early independence period. It uses outdated pedagogy, lacks professional relevance and fails to attract a diverse range of students. Through contrasting case studies, the paper examines, therefore: (i) the potential to move curriculum towards a problem‐based learning pedagogy where students focus on real‐world problems and associated engineering solutions; and (ii) the contribution of diverse case studies to this pedagogy and the content of courses. We argue that these twin shifts will broaden the curriculum beyond its habitual industry and physical infrastructure focus, is attractive to a wider range of students and links to human development as expressed through the United Nations sustainable development goals. It is also a major component in the pursuit by African institutions for international recognition of the quality of their engineering programmes. © 2019 John Wiley & Sons, Ltd.